Trypanotolerant livestock in West and Central Africa. Volume 3. A decade's results - Hoste, Christian H.; Chalon, E.; D'Ieteren, G.D.M.; Trail, J.C.M. (International Livestock Centre for Africa, 1992)
This volume presents major results obtained since the publication of volume 1 and 2 and updates national data on trypanotolerant cattle. The first part analyses populations and their trends between the two surveys and reviews research activities and development activities. It also gives recent information available on the potential and utilisation of trypanotolerant livestock. Part two presents recent data for the 18 study countries, as well as for Equatorial Guinea which was not covered in volume 2. This information should be studied in conjuction with volume 2 for an overall and updated view of trypanotolerant livestock production in each country. Countries are discussed in the same order in both volumes. An additional section on major developments occuring during the study period has been included at the end of each country study.